Hukum yang Hidup dalam Masyarakat dalam Pembaharuan Hukum Pidana Nasional - Tongat Tongat; Said Noor Prasetyo; Nu'man Aunuh; Yaris Adhial Fajrin (Jurnal Konstitusi, 2020)
The question about the existence of the living law in the criminal law reform can at least be done both in juridical and theoretical perspectives. This paper attempts to discuss and present two important perspectives on the living law in the criminal law reform. First, how the position of the living law in the criminal law reform is seen from the perspective of legal theory. Secondly, how far of the living law is gaining justification for contributing to the criminal law reform. Both problems are studied in doctrinal and produce findings as follows: first, the contribution of the living law in the criminal law reform is gaining theoretical strengthening. Secondly, the contributions of the living law in the criminal law reform also obtained not only by national legal instruments, but also by international legal instruments.